1988
DOI: 10.1037/0097-7403.14.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous transfer of matching by infant chimpanzees (Pan troglodytes).

Abstract: Four infant chimpanzees learned a matching-to-sample task when only two training stimuli were used. They then spontaneously transferred the matching concept to novel items, including three-dimensional objects and fabric swatches, without any experimenter-provided differential feedback. These results support the view that the matching concept is broadly construed by chimpanzees from the beginning and does not depend upon explicit training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
5
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 47 publications
3
114
5
5
Order By: Relevance
“…Premack (1983b) reported that conceptual-relational matching was expressed by only those of his chimpanzees who had a history of 'language training'. This observation was further confirmed by the finding that infant chimpanzees without prior experience with a token based symbol system failed to match conceptually despite their success on a generalized matching task based on physical resemblance between objects (Oden, Thompson, & Premack, 1988;1990). As noted previously, these animals spontaneously transferred their matching ability to novel objects after initial training with only two objects, a lock and a cup.…”
Section: Profound Disparities In Conceptual Relational Abilitiessupporting
confidence: 65%
See 3 more Smart Citations
“…Premack (1983b) reported that conceptual-relational matching was expressed by only those of his chimpanzees who had a history of 'language training'. This observation was further confirmed by the finding that infant chimpanzees without prior experience with a token based symbol system failed to match conceptually despite their success on a generalized matching task based on physical resemblance between objects (Oden, Thompson, & Premack, 1988;1990). As noted previously, these animals spontaneously transferred their matching ability to novel objects after initial training with only two objects, a lock and a cup.…”
Section: Profound Disparities In Conceptual Relational Abilitiessupporting
confidence: 65%
“…Good evidence of a broadly construed reflexive concept of physical identity was revealed in infant chimpanzees (Pan troglodytes) by Oden, Thompson, & Premack (1988) using a matching task (cf., Nissen, Blum, & Blum, 1948). Visual (and auditory) generalized matching is facilitated in both old-and new-world monkeys when a large stimulus pool of objects is used as opposed to a limited sample set (cf., D'Amato, Salmon, & Columbo, 1985;Wright, Shyan, & Jitsumori, 1990).…”
Section: What Constitutes Evidence Of An Identity Concept?mentioning
confidence: 99%
See 2 more Smart Citations
“…Acquisition of an identity concept in matchingto-sample can be inferred from successful transfer to novel sample stimuli following acquisition with only two stimuli serving alternatively as the sample and nonmatching choice during training (Oden et al, 1988). If novel stimuli only are used on each trial during training, then the transfer of matching may in fact be mediated on the basis of either absolute or relative familiarity and novelty, rather than on the basis of reflexive identity.…”
Section: Categorisation Of Abstract Relationsmentioning
confidence: 99%